An Investigation into the Relationship between Audit Quality and Its Factors: Evidence from the FTSE 100 - Jia, M (2013)
The subject of the paper is to investigate the relationship between audit quality and its factors (including the audit client size, capital structure, audit fees, non-audit service fees, Big 4, firm tenure and cash from operations) during the financial crisis. The data of FTSE 100 from 2007 to 2011 will be selected as a sample for the study. Here the discretionary accruals as the proxy for audit quality will be calculated by Jones model and modified Jones model. Based on the prior studies, the regression model will be used to research the study. After the data and results analysis, it finds that the economic conditions and the method that can be used to measure the discretionary accruals may affect the relationship between audit quality and its seven factors. The paper contributes to extending the research field about related studies. It provides a new factor of economic conditions that can be considered by the studies related to the audit quality.